Implementation of Environmental Care Character Education Through Healthy Schools at SD Negeri 17 Tanjungpandan - Lisa Retnasari; Lathifah Faiqoh Nabilah; Dadang Sundawa; Yayuk Hidayah; Lutfia Septiningrum (Departement of Mathematics Education, 2023)
The educational process has a close and inseparable relationship with the environment. The school and parents of students play an important role in coaching students to improve their healthy lifestyles. The purpose of this study was to describe the implementation of the character of environmental care education through healthy schools and find out what are the inhibiting and supporting factors in improving healthy schools in SD Negeri 17 Tanjungpandan. Type of this research is a descriptive qualitative research approach. The subjects in this study consisted of school principals, teachers, and students at SD Negeri 17 Tanjungpandan. The techniques used in this research are observation, interviews, and documentation. The validity of the data in this study used source triangulation and technique triangulation, then analyzed by data collection, data reduction, data presentation, and drawing conclusions.The results of this study indicate that the implementation of environmental care character education through healthy schools at SD Negeri 17 Tanjungpandan is integrated into learning which goes through the planning, implementation, and evaluation stages of learning. In addition, the implementation of environmental care character education is also carried out based on school policies, school programs, as well as environmental activities and management of facilities and infrastructure supporting healthy schools. Environmental care character education is also carried out based on school policies, school programs and environmental activities, as well as management of facilities and infrastructure that support healthy schools. Factors supporting the implementation of ecologically responsible character education in this healthy school are collaboration between school members and parents of students, as well as being supported by facilities and infrastructure. At the same time, the inhibiting factors are from the internal scope itself, such as some students who are still unaware of caring for the environment.